Impact of Two Diets on Metabolic- and Exercise-Based Outcomes to Workouts on Gravity-Independent Hardware (P23-002-19). (13th June 2019) - Vanhoover, Alexandria; McEnroe, Charles; Gray, William; O'Brien, Ian; Kozerski, Amy; Crush, Emma; Selimovic, Ema; Carter, Kathy; Caruso, John
Abstract: Objectives: Space flight diets include a 55/30/15 (carbohydrate/fat/protein) ratio. Yet recent long-term missions require astronauts to exercise several hours daily for up to seven days a week. We hypothesize a high protein diet (45/25/30) is more conducive to longer missions and their high volumes of exercise. Methods: With a within-subjects design, participants (8 men, 8 women) adhered to each diet for 14 days. Isocaloric diets were prescribed based on subject's resting metabolic rate, activity level and body composition. Compliance was monitored daily. Per subject, diet sequence was randomized to limit order effects. Immediately after each diet concluded subjects worked out on a gravity-independent device (Impulse Training Systems; Newnan, GA) while tethered to a metabolic cart. Workouts entailed four (unilateral knee extension, unilateral hip extension, unilateral standing row, bilateral arm pulldown) exercises, comprised of three 60-second sets separated by 60-second rests and done against 4.4 kg. Work volumes were measured from our device, as were pre-exercise respiratory quotients (RQ), and energy costs based on net O2 uptakes. Blood lactate concentrations ([BLa-]) were measured before and five minutes after workouts. Exercise and respiratory data were compared with 2(gender) × 2(diet) ANOVAs, with repeated measures for diet. [BLa-] were assessed with a 2(gender) × 2(time) × 2(diet) ANOVA, with repeated measures for time and diet. Results: Significant [BLa-] differences occurred for time (post > pre) and for RQ by diet (55/30/15 > 45/25/30). Trends for work differences occurred by gender (men > women) and diet (45/25/30 > 55/30/15). Conclusions: Our preliminary results concur with those that show greater RQ values from diets higher in carbohydrates. With continued data collection it is of interest to note if inter-work differences reach statistical significance, with higher values produced by the high protein diet. If so, such a diet may be more efficacious as a countermeasure to the muscle atrophy, strength loss and performance decrements for in-flight operational tasks seen with longer missions. Funding Sources: Kentucky Space Grant Consortium.